2000
DOI: 10.1046/j.1442-2050.2000.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Barrett’s esophagus by endoscopy and histologic studies: a prospective evaluation of 306 control subjects and 376 patients with symptoms of gastroesophageal reflux

Abstract: The classic endoscopic diagnosis of a Barrett's esophagus (BE) is based on the finding of > or =3 cm, of distal esophagus covered by specialized columnar epithelium. However, currently, it is based on the finding of intestinal metaplasia (IM) at the squamous-columnar mucosal junction, independent of its extent. The aim of this study was to determine the prevalence of Barrett's esophagus by endoscopic and histological findings in control subjects and in patients with symptoms of gastroesophageal reflux (GER). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 21 publications
3
52
1
9
Order By: Relevance
“…Comparative studies have confirmed a higher prevalence of dysphagia and more impaired esophageal bolus transport in Barrett’s versus non-Barrett’s GERD patients [71,72,73]. In addition, esophageal peptic ulcer or stricture are significantly more frequent among patients with ‘long-segment’ Barrett’s esophagus, and this may also contribute to dysphagia symptom generation [74]. A matter of ongoing controversy is whether the poorer motility in Barrett’s esophagus affects the occurrence of dysphagia after antireflux surgery.…”
Section: Esophageal Dysmotilitymentioning
confidence: 96%
“…Comparative studies have confirmed a higher prevalence of dysphagia and more impaired esophageal bolus transport in Barrett’s versus non-Barrett’s GERD patients [71,72,73]. In addition, esophageal peptic ulcer or stricture are significantly more frequent among patients with ‘long-segment’ Barrett’s esophagus, and this may also contribute to dysphagia symptom generation [74]. A matter of ongoing controversy is whether the poorer motility in Barrett’s esophagus affects the occurrence of dysphagia after antireflux surgery.…”
Section: Esophageal Dysmotilitymentioning
confidence: 96%
“…Reflux symptoms are common in Western populations, 34,35 but when such patients are referred for endoscopy, some have no visible pathology, some have developed esophagitis, and others have developed the precancerous lesion of BE, 36 which is associated with an increased risk of progression to EAC. In an attempt to improve EAC prognosis with an early diagnosis, the American College of Gastroenterology recommends the enrollment of all BE patients in endoscopic surveillance programs.…”
Section: Discussionmentioning
confidence: 99%
“…36 As both patients and controls in this investigation were recruited from dyspepsia and Barrett endoscopy clinics, a major strength of our study is that all patients had undergone endoscopic examination to allow inclusion into the appropriate study group. As a result, however, our study is limited by the relatively small number of patients recruited, implying that the role of this polymorphism in esophageal carcinogenesis needs to be further clarified in the context of a larger investigation.…”
Section: Discussionmentioning
confidence: 99%
“…nonacid reflux) and is not always a perfect standard [8]. Oesophageal endoscopy is usually performed when severe symptoms are present or when a complication is suspected and systematic biopsies must be taken to confirm oesophagitis, or to detect Barrett's oesophagus [9]. Radiological reflux evaluation, which was proposed in the early 1950s, is also used to diagnose the morphological aspects of the disease, such as stenosis and the presence of hiatal hernia (HH) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Tuttavia l'impiego della pH-metria è limitato a causa della sua invasività, del suo costo, della sua durata, della scarsa tolleranza e della ridotta disponibilità sul territorio [7]; inoltre la pH-metria può misurare l'esposizione acida della mucosa esofagea ma non può rilevare gli episodi di reflusso con pH >4 (cioè reflusso non acido) e, per questo, non si può considerare un test perfetto [8]. L'endoscopia esofagea viene riservata a pazienti con sintomi severi o con sospette complicanze della malattia da reflusso quali l'esofagite e/o l'esofago di Barrett, per la cui diagnosi è necessario effettuare biopsie multiple della mucosa [9]. La valutazione radiologica, che fu proposta sin dall'inizio degli anni Cinquanta, è solitamente usata per diagnosticare le alterazioni morfologiche della malattia, quali stenosi ed esofagiti, e la presenza di ernia iatale [10,11].…”
Section: Introduzioneunclassified